Optochemical Control of Immune Checkpoint Blockade via Light‐Triggered PD‐L1 Dimerization. Issue 6 (16th May 2022) - Liu, Yuwei; Long, Kaiqi; Kang, Weirong; Wang, Tianyi; Wang, Weiping
Abstract : The blockade of PD‐1/PD‐L1, which serves to "release the brake" of tumor immunity, represents a promising approach for treating various malignancies. However, the systemic immune‐related side effects significantly undermine its therapeutic efficacy. To address this dilemma, a photoactivatable and biocompatible prodrug cBMS‐1 based on the concept of photopharmacology is reported. The prodrug exhibits negligible toxicity but exerts effective PD‐1/PD‐L1 axis inhibition upon light irradiation, holding promising potential to achieve local activation of immune responses in clinical settings. Abstract : A photoactivatable and biocompatible prodrug is developed, which exhibits negligible cytotoxicity but exerts effective PD‐1/PD‐L1 axis inhibition upon light irradiation. The light‐triggered immune checkpoint blockade controls biological functions of immune cells in a precisely controlled way.